Effects of nano-bioactive glass on structural, mechanical and bioactivity properties of Poly (3-hydroxybutyrate) electrospun scaffold for bone tissue engineering applications. (29th July 2019) - Iron, Razieh; Mehdikhani, Mehdi; Naghashzargar, Elham; Karbasi, Saeed; Semnani, Dariush
ABSTRACT: 3-D nanocomposite scaffolds have recently had wide applications in bone tissue engineering. In this study, 58S bioactive glass nanoparticles (nBGs) were synthetized using sol-gel method and characterized. According to the results, the size of nanoparticles was achieved less than 100 nm. In the following step, Poly (3-hydroxybutyrate) (P3HB) was reinforced with 7.5, 10 and 15 %wt. of nBGs. Then, nanocomposite scaffolds were prepared by electrospinning technique and the structure was characterized structurally and mechanically. The results show that nanocomposite scaffolds have interconnected porosity with proper distribution and interaction of nBGs with polymeric nanofibres. Finally, The bioactivity of the optimized scaffold was evaluated by soaking in the simulated body fluid for 21 days and results obtained the P3HB/nBG electrospun scaffolds are bioactive as the apatite layer was observed on the surface of the fibres. To sum up, P3HB/nBG electrospun scaffold could be a very good candidate for bone tissue engineering applications.